BRANCHES OF UZBEK LEXICOLOGY IN LINGUISTICS - Xusniddinova Nazokat Fazliddin qizi; Xakimbayeva Ozoda Kalandarovna (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
Lexicology is considered main and fundamental branch of linguistics. Its role in modern science and interrelation with other field is thoroughly analyzed. In this article theoretical foundations of lexicology’s components (lexicography, phraseology, semasiology, semantics, etymology, stylistics) are highlighted. The author focuses on the nature and structure of the word, emphasizing it as an integral part of a linguistic system rather than an isolated unit.